2015
DOI: 10.1002/ccd.25735
|View full text |Cite
|
Sign up to set email alerts
|

PFO closure with only fluoroscopic guidance: 7 years real‐world single centre experience

Abstract: In our experience Fluoro-G PFO closure was performed mainly in cases of simple anatomy, with similar results in terms of safety and efficacy compared to Echo-G cases. Both fluoroscopy and total procedural times were lower in the Fluo-G cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 20 publications
0
15
2
Order By: Relevance
“…Transesophageal echocardiography (TEE) guidance also allowed a reduction in radiological exposure, both expressed in time of fluoroscopy and dose‐area product. This finding is in contrast to recently published data showing lower fluoroscopy time in angiography‐guided vs TEE‐guided procedures (7.6 ± 6 vs 10.6 ± 8 minutes). Of note, this study reported higher time of exposure, overall and in each subgroup, if compared to our results .…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Transesophageal echocardiography (TEE) guidance also allowed a reduction in radiological exposure, both expressed in time of fluoroscopy and dose‐area product. This finding is in contrast to recently published data showing lower fluoroscopy time in angiography‐guided vs TEE‐guided procedures (7.6 ± 6 vs 10.6 ± 8 minutes). Of note, this study reported higher time of exposure, overall and in each subgroup, if compared to our results .…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is in contrast to recently published data showing lower fluoroscopy time in angiography‐guided vs TEE‐guided procedures (7.6 ± 6 vs 10.6 ± 8 minutes). Of note, this study reported higher time of exposure, overall and in each subgroup, if compared to our results . Another study, on the contrary, confirms our results with even lower mean total fluoroscopic time of 3.4 ± 1.9 minutes .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Interventional PFO closure is usually performed using fluoroscopy and transesophageal echocardiography (TEE) guidance. Some experienced interventional cardiologists even perform PFO closure using fluoroscopy navigation only [7,8]. However, standby of TEE is necessary for any PFO closure in case of some cases with complicated anatomy of PFO.…”
Section: Introductionmentioning
confidence: 99%